Internationalization and bank financing of French SMEs - Bouslama, Ghassen; Boubacar, Hamadou (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
This study examines the effects of French small- and medium-sized enterprises’ (SMEs) internationalization on these firms’ bank financing. Using exporting activity and internationalization through foreign subsidiaries as proxy variables, we empirically examine the consequences of these two modes of internationalization on these firms’ bank debt ratios. Based on a dataset of French SMEs, the results show that exporting SMEs have more difficulty obtaining bank debt than those with subsidiaries abroad, SME’s exporting intensity is negatively associated with their bank debt ratios and foreign subsidiaries’ geographic proximity to their home firms is positively associated with SMEs’ bank debt ratios. These results suggest that each mode of internationalization leads to different financing behaviors.